2020
DOI: 10.18860/jetle.v2i1.10127
|View full text |Cite
|
Sign up to set email alerts
|

Student’s response in online learning process: A case study of English Education students

Abstract: The purpose of this study was to look at the level of student activity in online lectures. This research method uses descriptive qualitative. In this research, the data source is all online lecture recording one of the colleges in Madiun contained in the online media platform used by the author. The research results found several exciting things that the level of activity of students in the discussion is excellent compared with offline lectures. Several things can affect, such as the level of student confidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In this present study too, the majority of the participants were satisfied with this mode of learning as the students could do their school work in the comfort of their home which was similar as they need not wake up so early to go to school [30]. A study presented in a conference at Singapore showed that there were no significant differences between the academic performance of students in online learning and face to face learning whereas in this study, the academic performance of the majority of the participants was affected [30,31]. Another study showed that there is a significant relationship between daily stress and anxiety and the occurrence of health problems [17].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In this present study too, the majority of the participants were satisfied with this mode of learning as the students could do their school work in the comfort of their home which was similar as they need not wake up so early to go to school [30]. A study presented in a conference at Singapore showed that there were no significant differences between the academic performance of students in online learning and face to face learning whereas in this study, the academic performance of the majority of the participants was affected [30,31]. Another study showed that there is a significant relationship between daily stress and anxiety and the occurrence of health problems [17].…”
Section: Discussionmentioning
confidence: 54%
“…Due to the pandemic, the daily routine has been disrupted which affects the mental health and causes confusion, anger and boredom. This is also observed among a few school students [30][31][32][33]. Our previous research work experience has led us to carry out the present survey on current situations [34][35][36][37].…”
Section: Discussionmentioning
confidence: 58%